IMAGE COMMUNICATION BEFORE DEMOCRACY PARTY - Cevi Taufik (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
Politics ahead of the contestation cannot be separated from efforts to build an image. The key is to take advantage of the available time to optimize your appearance. Through visual polish and captivating narratives, the media is used as a means of channeling the desire for power. No matter the bad past track record, the quality and competence are still below average, all these shortcomings can be covered by packaging the symbol in such a way. Emphasis on the function of media influence, more emphasis on messages that explain that the figure who is being imaged as the successor of the national leadership has been conveyed. It's just that it is impossible to act openly by asking for support from the community, considering the rules forbid it. Instead, use the media as a manipulation tool to conjure up politicians to be popular in the eyes of their constituents. With regard to this theme, the research aims to reveal the messages used in political socialization. The approach used is a qualitative method with semiotic analysis techniques regarding the signs used by politicians in building self-image in the community. Keywords: politics, message, socialization